2020
DOI: 10.1073/pnas.2005463117
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic candidates for the Zika virus identified by a high-throughput screen for Zika protease inhibitors

Abstract: When Zika virus emerged as a public health emergency there were no drugs or vaccines approved for its prevention or treatment. We used a high-throughput screen for Zika virus protease inhibitors to identify several inhibitors of Zika virus infection. We expressed the NS2B-NS3 Zika virus protease and conducted a biochemical screen for small-molecule inhibitors. A quantitative structure–activity relationship model was employed to virtually screen ∼138,000 compounds, which increased the identification of active c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…The activity of their compound was comparable with our compound 1 in the cell culture model. Rachel et al identified the five-lipoxygenase-activating protein inhibitor, MK-591, inhibiting the ZIKV protease and infection in neural stem cells [ 27 ]. The IC 50 was higher (3 µM) than our compound 1.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of their compound was comparable with our compound 1 in the cell culture model. Rachel et al identified the five-lipoxygenase-activating protein inhibitor, MK-591, inhibiting the ZIKV protease and infection in neural stem cells [ 27 ]. The IC 50 was higher (3 µM) than our compound 1.…”
Section: Discussionmentioning
confidence: 99%
“…A few recent examples illustrate these features in DPI's publications: a serosurvey of COVID-19; 25 molecular targets and pathways for organ level toxicity; 26 computational methods in metabolomics; 27 targeting cancer mutations with kinase inhibitors; 28 and therapeutic candidates for the Zika virus. 29 These publications [25][26][27][28][29] demonstrate the quality and public health impact of the research. Table 2 links the major findings of these studies to the performance metrics in Figure 2, providing a deeper analysis of the scientific contributions of the studies represented in this sample of DPI manuscripts.…”
Section: Discussionmentioning
confidence: 99%
“…For cost efficiency, validated predictive methods and assays for early elimination of potential drug candidates are of great value 59 . The overall efficiency (time, costs, safety) prompts to suggest implementing PHENSIM not only in viral acute pandemic settings 60 , but in additional curative and noncurative diseases, especially complex chronic disorders, where clinical trials are timeconsuming or impossible to reduce to practice. Optimally leveraging the power of pathway analysis by simulating host cell and tissue-specific infection and performing in silico drug selection, has a tremendous potential beyond COVID-19, with applicability to high global burden communicable diseases, translatable to pathogens of viral, bacterial and fungal origin, and potentially chronic disease such as inflamm-aging and diabetes.…”
Section: Discussionmentioning
confidence: 99%